PENGUKURAN TINGKAT KAPABILITAS APLIKASI MOBILE BANKING DENGAN MENGGUNAKAN FRAMEWORK COBIT 5 PADA DOMAIN APO DAN DSS (STUDI KASUS: BANK NEGARA INDONESIA (BNI) FATMAWATI) - Fanny Krisnawaty Br Samosir, (2020)
The application of information technology has an important role for both government and private organizations. The development of information technology has become a competition between banks in providing the best service to customers. By following the development of increasingly sophisticated technology in all fields, banks continue to innovate by providing m-Banking services, without exception Bank Negara Indonesia (BNI) provides BNI Mobile Banking (m-Banking) services, which are banking service facilities that make it easy for customers to conduct transactions directly using a smartphone. In achieving the BNI mission, the BNI Mobile Banking Application as a form of implementation of services provided to BNI customers must be assessed and evaluated to improve service. The assessment of resource performance optimization is done by utilizing the COBIT framework 5. Researchers focus on measuring Capability Level in the process of Managing Relationships (APO0.05.05), Managing Quality (APO11), Managing Service and Incident Assistance (DSS02), Managing Problems (DSS03) , Managing Security Services (DSS05). From the evaluation results, it is known that all processes assessed in this study as a whole are at capability level 3 (three) where almost all processes have achieved their objectives with the target level to be achieved is 5 (five).